2020
DOI: 10.1016/j.jad.2020.03.185
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and psychiatric correlates of suicidal ideation in UK university students

Abstract: Data will be made available on reasonable request. Declaration of Competing Interests: No conflicts of interest declared in relation to this paper. Contributors: All authors contributed to developing the design of this study and data collection. Data was analysed by UA. Interpretation of results was conducted by UA. An initial version of the manuscript was written by UA. Following, input was sought from all other authors who approved the final version of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 55 publications
4
50
0
1
Order By: Relevance
“…Nevertheless, prevalence of mental ill-health in the current sample of PGRs is comparable to that reported by postgraduates in other countries (e.g. Evans et al, 2018;UC Berkeley Graduate Assembley, 2014), and undergraduates in the UK (Akram et al, 2020;McIntyre et al, 2018), and elsewhere (cf. Alvi et al, 2010;Ibrahim & Abdelreheem, 2015;Moutinho et al, 2017;Wong et al, 2006).…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, prevalence of mental ill-health in the current sample of PGRs is comparable to that reported by postgraduates in other countries (e.g. Evans et al, 2018;UC Berkeley Graduate Assembley, 2014), and undergraduates in the UK (Akram et al, 2020;McIntyre et al, 2018), and elsewhere (cf. Alvi et al, 2010;Ibrahim & Abdelreheem, 2015;Moutinho et al, 2017;Wong et al, 2006).…”
Section: Discussionsupporting
confidence: 78%
“…University students are young adults, and research has shown that the levels of loneliness, mental health problems, and suicidality were higher in this group as compared to the general population in the pre-pandemic era ( Akram et al, 2020 ; Ibrahim, Kelly, Adams, & Glazebrook, 2013 ). Data from the UK Office for National Statistics also indicated that, as of November 2020, University students in the UK reported higher anxiety scores than the general population, and more than half experienced mental health deterioration.…”
Section: Studymentioning
confidence: 97%
“…College students have traditionally been identified as one of the most vulnerable groups in developing mental health problems compared to their counterparts that are not in tertiary education [23][24][25], coinciding with a heightened risk of suicidal behavior [26][27][28]. However, the context of the COVID-19 pandemic has new implications for the psychological effects affecting this collective of young people.…”
Section: Introductionmentioning
confidence: 99%